Pembinaan Warga Gereja bagi Jemaat Korban KDRT: Perspektif Teologi Pastoral - Simon, Simon; Pardede, Zulkisar; Tandiongan, Fianus (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
Abstract: The author of this study, Dasariah, starts from the increasing prevalence of domestic violence in Christian families. The result of this domestic violence is a high divorce rate. The writing of this topic is also based on the church's seeming tendency to still rely on normative advice and prioritise textual interpretation to create Christian family wholeness, without addressing the problems of congregants who are victims of domestic violence. The main research question formulated in this study is: How can the development of church members be framed as a pastoral practice that supports the recovery of victims of domestic violence? In elaborating on this topic, the researcher applied a qualitative method with a pastoral theological approach. The findings of this study indicate that domestic violence experienced by the congregation often takes various forms. Often, the church responds to congregants experiencing domestic violence in a normative manner, and the victim's issues are treated as secondary. That's why the church guides by creating a safe space for the congregation to speak honestly without fear, and by collaborating with counselling institutions to heal the wounds of congregants who have experienced domestic violence. Abstrak: Dasariah penulis kajian ini berangkat dari semakin maraknya kekerasan dalam rumah tangga yang terjadi dalam keluarga Kristen. Akibat dari KDRT ini menyebabkan tingginya angka perceraian. Penulisan topik ini juga didasarkan pada gereja yang seakan masih cenderung bertumpu pada pemberian nasihat bersifat normatif dan mengutamakan tafsir teks demi menciptakan keutuhan keluarga Kristen, tanpa penyelesaian problem jemaat yang menjadi korban KDRT. Rumusan pertanyaan penelitian utama yang diajukan dari kajian ini bagaimana pembinaan warga gereja dapat dirumuskan sebagai praksis pastoral yang berpihak pada pemulihan korban KDRT? Di dalam menguraikan topik ini, peneliti menerapkan metode kualitatif dengan pendekatan teologi pastoral. Hasil temuan kajian ini mengemukakan bahwa kekerasan dalam rumah tangga yang dialami oleh jemaat sering kali hadir dalam berbagai bentuk. Acap kali gereja merespons jemaat yang mengalami KDRT bersikap normatif dan masalah korban ditempatkan bersifat sekunder. Itu sebabnya gereja melakukan pembinaan dengan memberikan ruang aman bagi jemaat tanpa takut bersuara secara jujur, serta berkolaborasi dengan lembaga pendampingan guna penyembuhan luka jemaat yang mengalami KDRT.